Bishops Selection and Quality of the Episcopal Government in Central-Northern Italy during the Fourteenth Century: Some Research Notes (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
This paper focuses on the process of selection and appointment of bishops at the end of the Middle Ages, by trying to summarize a number of topics debated in recent historiography (both Italian and European). Particular attention has paid to the cultures of government that the bishops (and their agents) displayed in the management of the diocese.DOI 10.17464/9788867742769
Keywords: Bishops; 14th century; Papacy; episcopal government; dioceses; episcopal appointments